Human exploitation of carnivores in Pleistocene China: A case study of the faunal remains from Shuidonggou Locality 7 - Zhang, Shuangquan; Zhang, Yue; Pei, Shuwen; Gao, Xing (Science China. Earth sciences, 2020)
Hominin-animal interactions at Pleistocene archaeological sites have been the main subject of research during human evolution. However, in contrast to that of ungulates, little is known about the evidence of human processing of carnivore species in this time interval of China. In this paper, we present the first case report of an interactive relationship between carnivore species and hunter-gathers in Pleistocene China, based mainly on a detailed taphonomic study of the faunal remains from Shuidonggou Locality 7. It seems highly probable that hominins butchered some individuals of carnivores and roasted bone elements with adhering meat at the site; whereas it’s equally feasible that these animals were exploited by hominins mainly for their pelt or fur. In either way, evidence from the site indicates novel strategies in adaptive behaviors adopted by Late Pleistocene foragers in harsh environments of Northwest China.